Effects of non-fasting molting on performance, oxidative stress, intestinal morphology, and liver health of laying hens - Lei, Meng; Shi, Lei; Huang, Chenxuan; Yang, Yawei; Zhang, Bo; Zhang, Jianshe; Chen, Yifan; Wang, Dehe; Hao, Erying; Xuan, Fengling; Chen, Hui (Frontiers in Veterinary Science, 2023)
Animal welfare concerns in laying-hen production facilities have necessitated research on alternative strategies for improving egg production and hen health. At present, most laying-hen facilities in China use the fasting method, but with international emphasis on animal welfare, scholars have begun to find ways to improve production efficiency while ensuring animal welfare standards are adhered to. Therefore, this study investigated the effects of non-fasting molting on production performance, oxidative stress, intestinal morphology, and liver health of laying hens. A total of 180 healthy 90-week-old Dawu Jinfeng laying hens with similar body weights and laying rates (76 ± 2%) were randomly divided into three groups, with five replicates per group and 12 hens per replicate. The hens in the experimental group (NF) were molted using the non-fasting method, the negative control group (C) was not treated with centralized molting, and the positive control group (F) was molted using the fasting method. The results showed that: (1) During the molting period, the laying rate in the NF group (10.58%) decreased and was significantly lower than that in the other two groups (P < 0.05). During the secondary laying peak period, the laying rate in the NF group was highest (89.71%); significantly higher than that in the C group (P < 0.05). (2) During the molting period, compared to the C group, the NF group showed a significant decrease and increase in the total antioxidant capacity (T-AOC) and superoxide dismutase (T-SOD) activity, respectively (P < 0.05). During the secondary laying peak period, the T-SOD activity of the NF group was significantly lower than that of the C group (P < 0.05). (3) During the molting period, the villus height (VH) and the ratios of VH to crypt depth (V/C) of the duodenum, jejunum, and ileum in the NF group were significantly lower than those in the C group (P < 0.05). At the secondary laying peak period, the jejunum V/C was significantly higher than that in the C group (P < 0.05), whereas in the duodenum and ileum it increased but not significantly (P > 0.05). (4) During the molting period, serum glutathione transaminase (AST) and glutathione alanine transaminase (ALT) activities were significantly higher (P < 0.05), and very low-density lipoprotein (VLDL) content and liver weight were significantly lower (P < 0.05) in the non-fasted and fasted groups. However, there was a low degree of liver injury (cell boundary still visible) in the NF group. At the secondary laying peak period, there was no significant difference (P > 0.05) in the indices among the three groups and the liver returned to normal. In summary, non-fasting molting can improve the production performance of laying hens in the later stages, ensure the welfare and health of animals, and provide a theoretical basis for the efficient production of laying hens.